2015
DOI: 10.1108/md-04-2014-0222
|View full text |Cite
|
Sign up to set email alerts
|

Competitive strategy, capabilities and uncertainty in small and medium sized enterprises (SMEs) in China and the United States

Abstract: Purpose – The purpose of this paper is to investigate linkages among competitive strategy, strategic capabilities, environmental uncertainty, and organizational performance in small and medium sized enterprises (SMEs) in China and the USA. Design/methodology/approach – In China, a survey was administered to managers of SMEs in Shanghai and Guangzhou. In the USA, a survey was administered to managers of SMEs in three major cities. Competi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
103
0
34

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(154 citation statements)
references
References 124 publications
7
103
0
34
Order By: Relevance
“…Our findings strongly supported Anwar (2018) who found that CA is a significant factor that can enhance the performance of SMEs in Pakistan. Similarly, Parnell et al (2015) also argued that a firm with a sustainable competitive position in the market enjoys superior profitability.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our findings strongly supported Anwar (2018) who found that CA is a significant factor that can enhance the performance of SMEs in Pakistan. Similarly, Parnell et al (2015) also argued that a firm with a sustainable competitive position in the market enjoys superior profitability.…”
Section: Discussionmentioning
confidence: 99%
“…Both competitive strategies are associated with high performance of SMEs but not always (Parnell 2010). For instance, Chinese firms often tend to follow cost-based competitive strategies instead of a differentiating-based strategy which may require high financial capabilities and resources (Parnell et al 2015). Both strategies of Porter-cost leadership and differentiation-based-have a significant influence on the financial and non-financial performance of SMEs (Oyewobi et al 2015).…”
Section: Competitive Advantage and Sme Performancementioning
confidence: 99%
“…Cost-Leadership Strategy (Cronbach's Alpha = 0.828; AVE = 0.557) Our manufacturing costs were lower than our competitors' 0.713 Our efficient internal operation system decreased the cost of our products 0.800 Our economy of scale enabled us to achieve a cost advantage 0.741 We achieve a cost-leadership position in our industry 0.728 Measures of competitive strategy were adapted from Li and Li [19]. They have been demonstrated as being reasonably reliable and valid in the Chinese context [80,84]. Four items were used to operationalize differentiation strategy, reflecting the extent to which firms differentiate themselves from competitors in products and services.…”
Section: Constructs Factor Loadingmentioning
confidence: 99%
“…Very few studies have been carried out in the last two decades to discover the key factors that can prevent enterprises from continual failure (Wild, 2010;Collett, Pandit & Saarikko, 2014). There is confusion about the factors and actions likely to facilitate the success of enterprises (Liou & Smith, 2006;Laitinen, 2011;Parnell, Long & Lester, 2015). Thus, it seems that as of now there is no study that has been carried out to conclusively provide the meaning of success to MSMEs entrepreneurs.…”
Section: Definition Of Success and Critical Success Factorsmentioning
confidence: 99%
“…However, there is also an argument that strategic business planning is not feasible in MSMEs because of the volatile business environment in which most MSMEs operate (Pekkola, Saunila & Rantanen, 2016). As a result most MSMEs shun formal planning (Parnell et al, 2015). Previous research indicates existence of a clear relationship between lack of planning by MSMEs and business failure (Jayawarna, Macpherson & Wilson, 2007).…”
Section: Business Planningmentioning
confidence: 99%